Re-sculpting a sacred text : towards an acceptable poetic translation of the Psalms – exemplified by Psalms 131 and 150 - Watt, Milton Lewis (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.